CRC cards to support the development and maintenance of product configuration systems. (1st December 2008) - Haug, Anders; Hvam, Lars
This article presents a new definition of special Class, Responsibility and Collaboration (CRC) cards to be used for the development and maintenance of Product Configuration Systems (PCSs). CRC cards were introduced as an informal and user-friendly technique for teaching object-oriented modelling. These CRC cards are often applied in the early phases of a software development project to come up with design alternatives. In 1994, extended CRC cards, with the purpose of holding detailed descriptions of classes in structural diagrams, were incorporated into a procedure for the development and maintenance of PCSs. This procedure has since been applied in several configuration projects and further developed at the Centre for Product Modelling (CPM) at the Technical University of Denmark. However, the investigations of two companies that applies CRC cards to document the knowledge base of their PCSs showed that their CRC card layouts differ from the definitions by CPM in many respects. Therefore, this article proposes a new CRC card definition that incorporates the experiences from the studied cases together with other kinds of extensions. The proposed CRC-card definition improves the basis for the companies that take up the technique.